The Influence of Training and Work Discipline on Employee Performance at PT. Paraduta Servis Indonesia - Arif Priambudi; Rony Edward Utama (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of training and work discipline on employee performance at PT. Paraduta Servis Indonesia. Quality human resources are the main factor in the success of a company, so good training and implementation of work discipline are needed to improve employee performance. The research method used is quantitative research with an associative approach. The sample of this study was all employees of PT. Paraduta Servis Indonesia, totaling 45 people, with a saturated sample technique. Data collection was carried out through questionnaires distributed to respondents. The data obtained were analyzed using simple linear regression and hypothesis testing with the help of SPSS software version 26. The results of the study showed that work training and work discipline had a significant effect on employee performance. Training provided systematically improves employee skills and knowledge, while good work discipline reflects employee responsibility in carrying out their duties. The findings of this study are expected to contribute to companies in designing training strategies and managing work discipline to improve employee performance. In addition, this study can also be a reference for further research in the field of human resource management.